2020
DOI: 10.1097/j.pain.0000000000002119
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-mediated receptor degradation contributes to development of tolerance to MrgC agonist–induced pain inhibition in neuropathic rats

Abstract: Agonists to subtype C of the Mas-related G-protein-coupled receptors (MrgC) induce pain inhibition after intrathecal (i.t.) administration in rodent models of nerve injury. Here, we investigated whether tolerance develops after repeated MrgC agonist treatments and examined the underlying mechanisms. In animal behavior studies conducted in male rats at 4 to 5 weeks after an L5 spinal nerve ligation (SNL), the ability of dipeptide MrgC agonist JHU58 (0.1 mM, 10 μL, i.t.) to inhibit mechanical and heat hypersensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Conversely, endocytosis of receptors targeting lysosomes can lead to down‐regulation of protein hydrolysis and reduced signal transduction (Dores & Trejo, 2019; Whistler et al, 2002). It has been shown that ubiquitin mediated the endocytic transport and degradation of MrgC (Huang et al, 2021). In our study, treatment of N2a cells with 3MA and CQ, the autophagy‐lysosome inhibitors, inhibited the degradation of MrgC, suggesting that degradation of MrgC after ubiquitination may occur via the autophagy‐lysosome pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, endocytosis of receptors targeting lysosomes can lead to down‐regulation of protein hydrolysis and reduced signal transduction (Dores & Trejo, 2019; Whistler et al, 2002). It has been shown that ubiquitin mediated the endocytic transport and degradation of MrgC (Huang et al, 2021). In our study, treatment of N2a cells with 3MA and CQ, the autophagy‐lysosome inhibitors, inhibited the degradation of MrgC, suggesting that degradation of MrgC after ubiquitination may occur via the autophagy‐lysosome pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have shown that MrgC plays an important role in the development of BCP, and can inhibit Ca2+ inward flow in spinal cord neurons by regulating the expression and activity of G αi , N ‐methyl‐ d ‐aspartate receptor subunit 2B and neuronal nitric oxide synthase, thus effectively improving the pain behaviour of mouse model with BCP (Sun et al, 2019; Sun, Jiang, et al, 2016; Sun, Zhang, et al, 2016). Other study has shown that MrgC undergoes ubiquitination followed by enhanced receptor endocytosis and down‐regulation of receptor number, thereby down‐regulating signal transduction and agonist actions (Huang et al, 2021). Therefore, reversing the ubiquitination of MrgC receptors may play an integral role in regulating MrgC receptor numbers and signal transduction.…”
Section: Introductionmentioning
confidence: 99%